Pengaruh Body Shaming terhadap Self-Esteem Siswa SMP - Nani Barorah Nasution; Ernita Simanjuntak (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The existence of a standardized appearance or ideal body, both for men and for women, often triggers body shaming for people who do not comply with these standards. This study aims to investigate the effect of body shaming on students' self-esteem This research uses a quantitative method using survey questionnare. Population of this study were 242 students of SMPN 2 Datuk Lima Puluh, with 60 sample of students. The instruments given were a questionnaire of body shaming and self-esteem. Then the data were analyzed using simple linear regression. The results of the calculations in data analysis indicates that each addition of one unit of body shaming score will be followed by a reduction in the score of the level of self-esteem. Furthermore, the results of the correlation coefficient showed that there is an effect of Body Shaming on Self-Esteem of Junior High School.Abstrak: Adanya standarisasi penampilan tubuh yang ideal, baik bagi laki-laki maupun perempuan seringkali memicu terjadinya body shaming pada orang-orang yang tidak sesuai dengan standarisasi tersebut. Penelitian ini menguji Pengaruh Body Shaming terhadap Self-Esteem Siswa SMP. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi dalam penelitian ini adalah 242 siswa SMPN 2 Datuk Lima Puluh dengan sampel 60 siswa. Instrumen yang diberikan adalah angket body shaming dan self-esteem. Hasil analisas data s menggunakan regresi linier sederhana. menunjukkan bahwa setiap penambahan satu satuan skor body shaming akan diikuti oleh pengurangan skor tingkat self-esteem. Selanjutnya hasil koefisien korelasi menunjukkan data bahwa rhitung>rtabel (0,455>0,254). Maka dapat disimpulkan bahwa ada pengaruh Body Shaming terhadap Self-Esteem Siswa SMP Negeri 2 Datuk Lima Puluh Tahun Ajaran 2020/2021.